Prediction of preterm labor using ultrasound measurement of cervical length at 11 to 14 weeks and 18 to 20 weeks - Kumar, Laxman; Ughareja, Chand; Tailor, Darshit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preterm birth (PTB) is the most important problems that pose dilemmas for both the obstetrician and neonatologist, as it is the leading cause of perinatal morbidity and mortality around the world. Routine cervical length screening during early pregnancy can predict PTB. Objectives were to predict the PTB with the use of ultrasonographic cervical length measurement at 11-14 weeks and 18-20 weeks of gestation. Methods: This prospective observational study was conducted from 1st March 2024 till 31st March 2024 at department of obstetrics and gynaecology pacific institute of medical science Udaipur. Total 100 cases selected which are routinely advised for ultrasound during antenatal checkup at 11-14 weeks and 18-20 weeks. In this study all the analysis was performed using 10.0 version of statistical software SPSS. Results: In this study most women (49.0%) belonged to the age group of 26-30 years. 78.0% of women had term births and 22.0% of women had PTBs. It was observed that 12 women had cervical length <25 mm at 18-20 weeks and 83% of them had PTBs while 16.6% had term birth. Conclusions: Ultrasound measurement of cervical length in early pregnancy is a reliable and cost-effective method for screening of PTB. We observed that women with shorter cervix early on in pregnancy had a greater number of PTB s as compared to women with normal length of cervix.